A New Four-Scroll Chaotic System with a Self-Excited Attractor and Circuit Implementation - Sampath, Sivaperumal; Vaidyanathan, Sundarapandian; Sambas, Aceng; Afendee, Mohamad; Mamat, Mustafa; Sanjaya, Mada (International Journal of Engineering and Technology, 2018)
This paper reports the finding a new four-scroll chaotic system with four nonlinearities. The proposed system is a new addition to existing multi-scroll chaotic systems in the literature. Lyapunov exponents of the new chaotic system are studied for verifying chaos properties and phase portraits of the new system via MATLAB are unveiled. As the new four-scroll chaotic system is shown to have three unstable equilibrium points, it has a self-excited chaotic attractor. An electronic circuit simulation of the new four-scroll chaotic system is shown using MultiSIM to check the feasibility of the four-scroll chaotic model.